An Analysis of Instructions Based on Revised Bloom’s Taxonomy in the “Pathway To English” Textbook for Twelfth Grade Students - Rahayu Oktarini (Teaching English and Language Learning English Journal, 2022)
This study aims to determine the type of instruction based on the revised Bloom’s taxonomy and to determine the proportion of instruction based on the cognitive domain of revised Bloom’s taxonomy in the English textbook of “Pathway to English” for twelfth grade published by Erlangga in 2017. This research applied mixed method (qualitative and quantitative). Table checklist based on cognitive domain of Revised Bloom’s taxonomy was the instrument of this research. For the validity of the data, the researcher used inter rater reliability, because there are only two raters, the results of rater 1 and 2 are calculated using Cohen's Kappa. The result of the value of Kappa is 0.910 means that > 0.75 so it can be conclude the result of analysis data is in excellent level of agreement. The result showed this book is more concerned with LOTS than HOTS with the percentage of HOTS 56.52% and LOTS 43.48%. The proportion between HOTS and LOTS is almost balanced. The most dominant level of thinking in this book is Understanding (C2). It can be said that it has not fully met the 2013 curriculum standards of the Ministry of Education and Culture. It is suggest for teachers who use this book to be innovative, creative, even teachers can adapt from other sources in giving instructions to develop students’ critical thinking.